Solving Mixed Convection Near Stagnation-Point on a Vertical Surface using bvp4c Solver - Azizi, Anis Sulwana; Aman, Fazlina (Enhanced Knowledge in Sciences and Technology, 2025)
This investigation focused on mixed convection near a stagnation point on a vertical surface. It validates the transformation of partial differential equations (PDEs) into ordinary differential equations (ODEs) using similarity transformations and solves them numerically with the shooting technique in MATLAB’s bvp4c solver. The effects of parameters, such as velocity slip, thermal slip, mixed convection, and Prandtl number on velocity and temperature profiles are analysed. Results show excellent agreement with a reference study, confirming the approach’s validity. Increasing slip parameters thickens boundary layers while reducing surface friction and heat transfer. The findings enhance understanding of slip effects in fluid flow and heat transfer near stagnation points.